(untitled) (Research, Society and Development, 2020)
This work is a description of a methodological didactic proposal to promote interdisciplinarity, using the methodological way of STEAM Education. STEAM Education, (Sciences, Technology, Engineering, Arts and Mathematics), has as guiding principle the practical application of theoretical contents for problem solving. In this context, we used David Ausubel’s Theory of Meaningful Learning, known abbreviated as TML to support our proposal. According to the TAS, significant learning promotes the cognitive development of the student and places the teacher as the protagonist agent of the teaching process. Thus, the proposal described here is called Potentially Significant Teaching Unit, PSTU and results from research in national and international theoretical references which discuss pedagogical didactic methodologies and the specific roles of teachers and students in the teaching learning process.